ChemInform Abstract: Chiral Bifunctional Squaramide Catalyzed Asymmetric Tandem Michael‐Cyclization Reaction: Efficient Synthesis of Optically Active 2‐Amino‐4H‐chromene‐3‐carbonitrile Derivatives. Issue 7 (18th February 2014) - Hu, Keling; Lu, Aidang; Wang, Youming; Zhou, Zhenghong; Tang, Chuchi
Abstract An enantioselective cascade Michael addition/cyclization of ortho‐hydroxy‐nitrostyrenes (I) with malononitrile is developed using a chiral bifunctional squaramide derivative as catalyst.